Virtual Teaching and Learning Activities in the Schools during COVID-19 Period: Use and Effectiveness - Diyal, Suresh Bahadur; Pandey, Romkant (Innovative Research Journal, 2024)
This study investigates the state of online teaching and learning in schools during the COVID-19 pandemic, exploring challenges, strengths, weaknesses, and strategies to promote participation among students and teachers. Employing a mixed research method with an embedded design, both quantitative and qualitative data were gathered to provide a comprehensive understanding of the phenomenon. The study reveals widespread familiarity with online tools among educators and learners, despite initial hurdles such as poor internet connectivity and limited technology proficiency. However, shortcomings in student engagement and participation were observed, with many students exhibiting passive behavior during online classes. Concerns were also raised regarding the reliability of online assessments, highlighting the need for robust evaluation methods. Various obstacles to effective implementation, including internet accessibility and distractions at home, were identified. Recommendations for future practice include addressing internet access issues, providing LMS training for teachers, and promoting a conducive learning environment. This study offers valuable insights into the challenges and opportunities of online education during emergencies, guiding efforts to enhance its effectiveness in the future.